Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Pt. Enseval Putera Megatrading, Tbk Cabang Jambi - Muhammad Adi Fadilah; Edward Edward; Rohman Wilian (Jurnal Dinamika Manajemen, 2023)
This study aims to examine and analyze the effect of transformational leadership on employee performance with organizational commitment as an intervening variable at PT. Enseval Putera Megatrading, Tbk Jambi Branch. The analytical method used is descriptive quantitative analysis using PLS analysis tools. Based on the results of the study that transformational leadership style has no significant effect on the performance of employees of PT. Enseval Putera Megatrading, Tbk Jambi Branch. Organizational commitment has a significant and positive effect on the performance of PT. Enseval Putera Megatrading, Tbk Jambi Branch. The transformational leadership style has a significant and positive effect on the organizational commitment of PT. Enseval Putera Megatrading, Tbk Jambi Branch. Transformational leadership style has a significant and positive effect on employee performance with Organizational Commitment as the intervening variable of PT. Enseval Putera Megatrading, Tbk Jambi Branch.